Susceptibility of Orius insidiosus to Beauveria bassiana, Akanthomyces muscarius, and Cordyceps fumosorosea and their effects on predator behavior - Manfrino, Romina Guadalupe; Rocca, Margarita (Wiley, 2025)
The use of pathogens and other natural enemies to suppress pest populations is a key component of integrated pest management (IPM) strategies. As biocontrol agents may interact synergistically, additively, or antagonistically, it is crucial to assess their interactions for effective pest management. In this study, we investigated the effect of three entomopathogenic fungus (EPF) species—Beauveria bassiana (Bals.-Criv.) Vuill. CEP 091, Akanthomyces muscarius (Petch) Spatafora, Kepler & B. Shrestha CEP 182, and Cordyceps fumosorosea (Wize) Kepler, B. Shrestha & Spatafora CEP 315 (all Hypocreales)—on the survival, fecundity, and searching behavior of Orius insidiosus (Say) (Hemiptera: Anthocoridae). All three EPF species were found to be pathogenic to O. insidiosus, resulting in a significant decrease in survival compared with the control group. Fecundity remained unaffected by the fungal treatments. No effect of EPF on searching behavior of the predator was found. In relation to the searching behavior, individuals of 2 days post-infections remained in the food patch longer than individuals of 7 days post-infections, regardless of treatment. These findings provide valuable insights into the compatibility of EPF and O. insidiosus as combined biocontrol agents for managing whiteflies, aphids, and thrips. Understanding the interactions between EPF and predatory insects is crucial for developing IPM strategies that maximize pest control efficacy. Further studies should explore the long-term effects of EPF on O. insidiosus populations and their overall impact on pest management in agricultural systems.